Podwójne życie tłumacza - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2018)
Translator’s Double Life The manner of functioning of South Slavic literature translators in the social field is presented in the article as a case of “multiplied social participation”, participation in the “game”, which they treat as an incentive for cultural, intellectual and moral development in the individual and social dimension. Methodological considerations on the translation presented in the article are based on the concepts of Barnard Lahire, Pierre Bourdieu, and Roger Caillois. KEY WORDS: Bernard Lahire, Pierre Bourdieu, literary field, game, Roger Caillois, literary translation